Decolonization and the Decolonized - Memmi, Albert (Book collections on Project MUSE., 2014)
"In this time of global instability and widespread violence, Albert Memmi--author of the highly influential and groundbreaking work The Colonizer and the Colonized--turns his attention to the present-day situation of formerly colonized peoples. In Decolonization and the Decolonized, Memmi expands his intellectual engagement with the subject and examines the manifold causes of the failure of decolonization efforts throughout the world. As outspoken and controversial as ever, Memmi initiates a much-needed discussion of the ex-colonized and refuses to idealize those who are too often painted as hapless victims. He shows how, in light of a radically changed world, it would be problematic--and even irresponsible--to continue to deploy concepts that were useful and valid during the period of anticolonial struggle. Decolonization and the Decolonized contributes to the most current debates on Islamophobia in France, the "new" anti-Semitism, and the unrelenting poverty gripping the African continent. Memmi, who is Jewish, was born and raised in Tunis, and focuses primarily on what he calls the Arab-Muslim condition, while also incorporating comparisons with South America, Asia, Black Africa, and the United States. In Decolonization and the Decolonized, Memmi has written that rare book--a manifesto informed by intellect and animated by passion--that will propel public analysis of the most urgent global issues to a new level."--JSTOR website (viewed April 13, 2017).